2007
DOI: 10.1007/s00277-006-0231-0
|View full text |Cite
|
Sign up to set email alerts
|

Necrobiotic xanthogranuloma successfully treated with autologous stem cell transplantation

Abstract: Paraproteinemia can be complicated by necrobiotic xanthogranuloma. Therapeutic options for this progressive disease are limited, and there is no agreement on a single best strategy. We report the case of a patient with a massive periorbital infiltration narrowing the palpebral fissure and blinding the patient. Conventional myeloma therapy had only limited benefit in our patient. However, he was successfully treated with high-dose chemotherapy followed by autologous stem cell transplantation, rendering the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…Necrobiotic xanthogranuloma, a rare chronic disorder prevailing in the sixth decade, occurs in association with IgG monoclonal gammopathy (usually k subtype) in about 80% of patients. Although bone marrow examination may show plasmocytosis, true multiple myeloma is not frequent (10%) 44–46 . Cryoglobulinemia occurs in 8% of case.…”
Section: Associated Disordersmentioning
confidence: 99%
“…Necrobiotic xanthogranuloma, a rare chronic disorder prevailing in the sixth decade, occurs in association with IgG monoclonal gammopathy (usually k subtype) in about 80% of patients. Although bone marrow examination may show plasmocytosis, true multiple myeloma is not frequent (10%) 44–46 . Cryoglobulinemia occurs in 8% of case.…”
Section: Associated Disordersmentioning
confidence: 99%
“…Of note, the xanthomatous lesions of the 4 patients who received an immunomodulatory drug, usually in combination with dexamethasone, were considered to be improved in all cases. Variations in the MIg level were rarely reported and inconsistent: some reported a decrease in levels accompanied by an improvement in cutaneous lesions, 34,75 whereas others reported that skin lesions persisted despite a reduction in MIg levels. 76 …”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…46,[64][65][66][67] Extracutaneous lesions were reported in 23 cases (17.6%), including 6 patients with several localizations. They were pulmonary (n ϭ 7), 8 cardiac (n ϭ 6), 8,37 oral cavity (n ϭ 4), 38,65 orbital (n ϭ 3), 8 hepatic (n ϭ 2), 8,37 spleen (n ϭ 2), 8 medullar (n ϭ 1), 68 genital (penis; n ϭ 1), 34 mastoid (n ϭ 1), 32 facial nerve (n ϭ 1), 32 and renal (n ϭ 1). 69 In addition, splenomegaly was noted in 22 patients (17%) and hepatomegaly in 17 (13%), without any further information.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Cases of complete response of NXG to treatment with PUVA, systemic chemotherapy agents, and IVIg have been reported in the literature . More severe refractory cases associated with underlying plasma cell dyscrasias have been treated with stem cell transplant . Laser ablation may be another procedural technique to treat individual NXG lesions, with pain in such cases managed by regional nerve blocks .…”
Section: Reportmentioning
confidence: 99%